2022
DOI: 10.1021/acs.biomac.2c00823
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Hyperbranched Polymer Nanoparticles to Combat Intracellular Infection by Disrupting Bacterial Wall and Regulating Macrophage Polarization

Abstract: Intracellular bacterial infections pose a serious threat to public health. Macrophages are a heterogeneous population of immune cells that play a vital role in intracellular bacterial infection. However, bacteria that survive inside macrophages could subvert the cell signaling and eventually reduce the antimicrobial activity of macrophages. Herein, dual pH-responsive polymer (poly[(3-phenylprop-2-ene-1,1-diyl)bis(oxy)bis(enthane-2,1-diyl)diacrylate-co-Naminoethylpiperazine] (PCA)) nanoparticles were developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…At a neutral pH of 7.4, only a limited release was observed. However, in a more acidic environment with a pH of 5.5, there was a significant release of the cinnamaldehyde agent, with approximately 40% being released after 60 h …”
Section: Nanoparticle Preparation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a neutral pH of 7.4, only a limited release was observed. However, in a more acidic environment with a pH of 5.5, there was a significant release of the cinnamaldehyde agent, with approximately 40% being released after 60 h …”
Section: Nanoparticle Preparation Methodsmentioning
confidence: 99%
“…Gao et al sought to imbue a cinnamaldehyde-based HBP with pH responsiveness from its backbone. 421 This was achieved through pH labile aminoethylpiperazine moieties, and it was shown that the resultant biodegraded polymer fragments were able to inhibit the growth of bacteria by generating ROS. ROS responsiveness was also utilized by Zhang et al who imbued a PEG-based HBP with ROS responsiveness via tellurium.…”
Section: Star and Hyperbranched Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…An immunofluorescence staining assay was performed as previously reported with slight modifications. 37,38 RAW 264.7 cells were added to confocal dishes and incubated at 37 1C for 24 h. After culturing with 125 mg mL À1 ox-Dex-Se/Van for 24 h, paraformaldehyde (4%) was added to the confocal dishes. The cells were permeabilized with Triton-X (0.1%).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…For example, the delivery of the traditional Chinese medicine cinnamaldehyde into intracellular bacteria-infected macrophages using PCA nanoparticles directly disrupted the bacterial wall and induced the generation of low levels of ROS to promote macrophage M1 polarization, which enhanced its bactericidal effect. 129 In addition, with the advancement of genetic engineering, using biomaterials for targeted modification of macrophages in vitro and subsequent transfusion back into patients has also proven to be an excellent antibacterial strategy. For example, the use of vitamin C lipid nanoparticles to deliver AMP and cathepsin B (AMP-CatB) mRNA into macrophages specifically increased AMP-CatB protein levels in macrophage lysosomes, thereby enhancing the bactericidal effect of lysosomes and reducing the escape of drug-resistant bacteria and the formation of intracellular bacteria.…”
Section: Modulation Of Infection Microenvironment Using Immunomodulat...mentioning
confidence: 99%